An Independant Commission on Dams - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Under attack from all quarters for its propensity to finance expensive and destructive projects, the World Bank accepted in 1997 to cooperate with the International Union for the Conservation of Nature (IUCN) in establishing an independent World...